(+)‐Catechin, epicatechin and epigallocatechin gallate are important inducible defensive compounds against Ectropis grisescens in tea plants. (9th November 2021) - Li, Xiwang; Zhang, Jin; Lin, Songbo; Xing, Yuxian; Zhang, Xin; Ye, Meng; Chang, Yali; Guo, Huawei; Sun, Xiaoling
Abstract: The tea plant, Camellia sinensis (L.) O. Kuntze, is an economically important, perennial woody plant rich in catechins. Although catechins have been reported to play an important role in plant defences against microbes, their roles in the defence of tea plants against herbivores remain unknown. In this study, we allowed the larvae of Ectropis grisescens, a leaf‐feeding pest, to feed on the plants, and alternatively, we wounded the plants and then treated them with E. grisescens oral secretions (WOS). Both approaches triggered jasmonic acid‐, ethylene‐ and auxin‐mediated signalling pathways; as a result, plants accumulated three catechin compounds: (+)‐catechin, epicatechin and epigallocatechin. Not only was the mass of E. grisescens larvae fed on plants previously infested with E. grisescens or treated with WOS significantly lower than that of larvae fed on controls, but also artificial diet supplemented with epicatechin, (+)‐catechin or epigallocatechin gallate reduced larval growth rates. In addition, the exogenous application of jasmonic acid, ethylene or auxin induced the biosynthesis of the three catechins, which, in turn, enhanced the resistance of tea plants to E. grisescens, leading to the coordination of the three signalling pathways. Our results suggest that the three catechins play an important role in the defences of tea plants against E. grisescens .